Formation of Anti-Violence Character in Schools by PAK Teachers in the Framework of Conflict Resolution - Saingo, Yokabus Adi; Leobisa, Jonathan; Baok, Deciana Mese; Oematan, Delsi Oktoviana (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
The purpose of this study is to analyze the formation of anti-violence character in schools by PAK teachers in the framework of conflict resolution that applies qualitative methods with the FGD approach. Data sources were collected from 13 PAK teachers in SMK Se Kota SoE, Timor Tengah Selatan Regency, which were analyzed reductively by presenting the results of the study that, the conflict resolution approach in an effort to strengthen the anti-violence character by PAK teachers as a standard to realize the conduciveness and smoothness of teaching and learning activities in the school environment, as well as a preventive measure so that there is no more violent behavior, as well as a curative action in restoring the psychology, morals, and spirituality of school members. The formation of anti-violence character with a conflict resolution approach, namely giving freedom to every school member to get the opportunity to convey any problems including violence experienced by themselves or witnessed when socializing, willing to discuss problems without being passive or closed, being open to compromise in solving problems, willing to forgive each other so that there is no longer an intention to repay evil with evil, and there is an agreement/commitment to maintain order. The significance of this research is to produce an educational contribution of a strategic approach based on conflict resolution to be implemented by PAK teachers through anti-violence learning as part of character education, so that all school members can become increasingly aware of the need to work together to create a conducive and inclusive school, and be able to become a positive reflection for the wider community.